Cytokinin Signaling Downstream of the His-Asp Phosphorelay Network: Cytokinin-Regulated Genes and Their Functions - Kroll, Carlo K.; Brenner, Wolfram G. (Frontiers in Plant Science, 2020)
The plant hormone cytokinin, existing in several molecular forms, is perceived by membrane-localized histidine kinases. The signal is transduced to transcription factors of the type-B response regulator family localized in the nucleus by a multi-step histidine-aspartate phosphorelay network employing histidine phosphotransmitters as shuttle proteins across the nuclear envelope. The type-B response regulators activate a number of primary response genes, some of which trigger in turn further signaling events and the expression of secondary response genes. According to the current model of cytokinin signaling, after activation of the type-B response regulator-dependent genes, the signal splits up into multiple strands, each one leading to a different one of the multiple hormonal effects. Most genes activated in both rounds of transcription were identified with high confidence using different transcriptomic toolkits and meta analyses of multiple individual published datasets. In this review we attempt to summarize the existing knowledge about the primary and secondary cytokinin response genes in order to try connecting gene expression with the multitude of effects that cytokinin exerts within the plant body and throughout the lifespan of a plant. The accumulated knowledge about cytokinin-regulated genes is particularly helpful in modern semi-targeted mutagenesis approaches such as the recently published method of mutagenomics, which relies on previously identified signaling components.